Coleridge on dreaming : Romanticism, dreams, and the medical imagination - Ford, Jennifer (Cambridge University Press, 1998)
This book is the first in-depth investigation of Coleridge's responses to his dreams and to contemporary debates on the nature of dreaming, a subject of perennial interest to poets, philosophers and scientists throughout the Romantic period. Coleridge wrote and read extensively on the subject, but his richly diverse and original ideas have hitherto received little attention, scattered as they are throughout his notebooks, letters and marginalia. Jennifer Ford's emphasis is on analysing the ways in which dreaming processes were construed, by Coleridge in his dream readings, and by his contemporaries in a range of poetic and medical works. This historical exploration of dreams and dreaming allows Ford to explore previously neglected contemporary debates on 'the medical imagination'. By avoiding purely biographical or psychoanalytic approaches, she reveals instead a rich historical context for the ways in which the most mysterious workings of the Romantic imagination were explored and understood.
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Knowledge -- Psychology.; Coleridge, Samuel Taylor, -- 1772-1834 -- Et la psychologie.; Coleridge, Samuel Taylor, -- 1772-1834; Coleridge, Samuel Taylor -- 1772-1834; Coleridge, Samuel Taylor, -- (1772-1834) -- Psychologie.; Coleridge, Samuel Taylor.; Dreams in literature.; Poets, English -- 19th century -- Psychology.; Poetry -- Psychological aspects.; Dreams -- History -- 18th century.; Dreams -- History -- 19th century.; Romanticism -- England.; Dreams -- history; Literature -- history; Poetry as Topic -- history; Rêves dans la littérature.; Poètes anglais -- 19e siècle -- Psychologie.; Poésie -- Aspect psychologique.; Rêves -- Histoire -- 18e siècle.; Rêves -- Histoire -- 19e siècle.; Romantisme -- Angleterre.; POETRY -- English, Irish, Scottish, Welsh.; Dreams; Dreams in literature; Poetry -- Psychological aspects; Poets, English -- Psychology; Psychology; Romanticism; England; Traum -- Motiv; Traum; Dromen.; Romantiek.; Rêves -- Dans la littérature.; Poésie anglaise -- 19e siècle -- Aspect psychologique.; 1700-1899; Electronic books.; History